The strategy of financing of investments in Russian energy market - T N Sedash; E U Seregina; E B Tyutyukina (RUDN Journal of Economics, 2009)
This article is devoted to evaluation of financing strategies of investments in Russian energy market during its reform, i.e. its division into government-monopoly sector and competitive sector. The authors have discussed the main approaches to formation of financing strategies of investments, and done a comparative analysis of sources of financing in Russian and foreign energy companies in 2006-2007. They have also evaluated perspectives of attracting of various sources of financing in power generation companies and distribution grid companies. Analysis below examines perspectives of attracting various sources of financing in power generation and distribution grid companies.